The aid contract and the generational turnover in agriculture - Spoto, Giuseppe (Przegląd Prawa Rolnego, 2019)
The legal framework of the State budget for the year 2018 in Italy provided for measures to encourage the training and development of young entrepreneurs in order to help in the transfer of new generations into agricultural business management. Young people, aged between eighteen and forty, my now enter into an agreement with agricultural entrepreneurs who are over sixty-five years old or retired, to cooperate and share the business profits. During the period of coaching the young person will have to acquire the necessary skills. The contract may provide for eventual takeover by the young agricultural entrepreneur of the management of the business. The author examines the compatibility of the new rules with the agrarian law, showing some weak points that the legislator should have considered.